Penerapan Model Pembelajaran Discovery Learning Berpendekatan Etnosains untuk Mengetahui Profil Literasi Sains Siswa SMP - Wiwin Puspita Hadi*; Fatimatul Munawaroh; Irsad Rosidi; Winda Kusuma Wardani (Universitas Syiah Kuala, 2020)
Science literacy is a means for students to practice scientific thinking to solve problems in everyday life. Discovery learning with Madura Ethnoscience approach can improve scientific literacy skills. The aim was to determine the students' scientific literacy profile by applying discovery learning with the Madura ethnoscience approach. The study design used the one-shot case study method. The research subjects were 27 students of SMP Negeri 1 Labang Bangkalan Madura. Data collection used scientific literacy questions in the form of essay questions. Research showed students' scientific literacy skills based on the results of the literacy test, results obtained an average value of 67.93% with an average functional level of 71%, conceptual and procedural 65%, and multidimensional 66%. The average level of student's literacy ability is at level 3 of 10 students; level 4 as many as two students; level 5 as many as ten students; and five students are at level 6. The ability to explain phenomena scientifically, evaluate and investigate scientific, and interpret data and scientific evidence was based differences in each level in the aspect of competence.